The Use of Tiktok Education: The Impact on Student's Vocabulary Acquisition - Juwita, Juwita; Syahputra, Bambang Panca (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study is to assess how well students' acquisition of English vocabulary is improved by using TikTok Education. This study recruited eight active students from Universitas Muhammadiyah Sumatera Utara English Education Study Program. It used a pre-experimental one-group pretest-posttest design. Pre- and post-test data were gathered, and descriptive statistics and the paired t-test were used for analysis. The vocabulary scores of the children significantly improved from the pre-test to the post-test, with an average increase of 84%. The statistical significance of this improvement was validated by a paired t-test (p 0.001). There was a positive shift in the distribution of students' scores as well; most of them scored in the